0198 Psychomotor/Cognitive Effects, Pharmacokinetics and Safety of V117957, a Novel, Highly Potent and Selective Partial Agonist for Nociceptin/Orphanin-FQ Peptide (NOP) Receptors, Administered in Combination with Alcohol in Healthy Subjects. (27th May 2020) - Zhou, M; Harris, S; Cipriano, A; Kapil, R; He, E; Shet, M; Apseloff, G
Abstract: Introduction: V117957 is an investigational nociceptin/orphanin-FQ peptide (NOP) receptor partial agonist designed to treat insomnia by promoting sleep onset and maintenance with minimal residual next-day somnolence or psychomotor impairment. The satisfactory safety/tolerability profile of V117957 has been previously established in 200 healthy subjects with maximum doses at 30mg following a single oral administration and 10mg once daily for 2 weeks. The present study was conducted to assess the safety/tolerability and pharmacokinetics (PK) of V117957 with co-administered alcohol. Methods: A randomized, double-blind, double-dummy, placebo-controlled, balanced six-period crossover design was employed. Single doses (2mg, 6mg) of V117957 and placebo were administered orally to healthy subjects in the morning with and without alcohol (0.7g/kg). Pharmacodynamic (PD) effects of V117957 were assessed, and safety/tolerability and PK interactions were also characterized. The primary PD endpoints (body sway, Digit Vigilance Test, and numeric working memory) were measured through 12 hours postdosing. Results: Forty-eight subjects were enrolled and randomized; 46 completed. Compared with placebo, alcohol alone showed an impairment on psychomotor/cognitive performances through 2 hours postdose. V117957 alone showed a dose-dependent impairment. Compared with V117957 alone and alcohol alone, co-administration of alcohol and V117957 showed greater impairment until 8 hours postdose. No subject discontinued due to an adverse event (AE). No clinically meaningful treatment-emergent (TE) changes in clinical laboratory values, vital signs, SpO2 measurements, or 12-lead ECG results were observed. The most common TEAE was somnolence. All plasma and urine PK parameters for V117957 and alcohol were comparable when V117957 or alcohol was administered alone or in combination. Conclusion: Single oral doses of V117957, 2mg or 6mg, administered alone or in combination with alcohol in healthy subjects resulted in no notable PK interaction between V117957 and alcohol. A dose-effect relationship in the magnitude and duration of impairment was observed for most psychomotor/cognitive performance parameters. Greater effects of V117957 with alcohol were observed for most psychomotor/cognitive performance parameters up to 8 hours post-dose. Support: Funded by Imbrium Therapeutics, a subsidiary of Purdue Pharma L.P.